PDIA in action - and Andrews, Matt; Samji, Salimah (Center for International Development, Harvard University, 2021)
Learning from our experience in 2020, we asked the alumni of our HKS Implementing Public Policy (IPP) Executive Education program, if they wanted to work with our students on their nominated problems. Eight IPP alumni, William Keith Young, Adaeze Oreh, Milzy Carrasco, Kevin Schilling, Artem Shaipov, George Imbenzi, David Wuyep, and Raphael Kenigsberg, who had been trained on PDIA and implementation, signed up to work with our students. Thirty-seven students signed up to take the course beginning January 26th, 2021. The students worked across eight teams and adopted a problem driven approach to foster learning that could help their authorizers develop an action learning strategy to their nominated challenge. This book highlights the students’ work drawing from their blogs as well as the event series. There are 8 sections, one for each of the teams and the problems they worked on during the course. We hope you enjoy reading their stories! Scan the QR Code at the end of each section to learn more.